A case report on uncommon A2 subtype of blood group A (Indian Journal of Case Reports, 2019)
Blood group A has various subtypes with A1 being the most common. A2 and other weaker subtypes are less commonly encountered. The differentiation between A1and A2 is based on the reactivity of A1 cells but not A2 cells with anti-A1 lectin. A2 cells show increased reactivity with anti-H lectin. The incidence of A2 subtype is not known in this region. Here, we report an incidental case of A2 blood group in a 25-year male. Subgroups of blood group A can result in ABO blood group discrepancy and rarely may lead to hemolytic transfusion reactions. The case report highlights the need to be aware of such uncommon and rare blood groups and using anti-A1 lectin as a standardized protocol to prevent blood group incompatibility.